2008
DOI: 10.1104/pp.108.115832
|View full text |Cite
|
Sign up to set email alerts
|

The MADS-Domain Transcriptional Regulator AGAMOUS-LIKE15 Promotes Somatic Embryo Development in Arabidopsis and Soybean

Abstract: The MADS-domain transcriptional regulator AGAMOUS-LIKE15 (AGL15) has been reported to enhance somatic embryo development when constitutively expressed. Here we report that loss-of-function mutants of AGL15, alone or when combined with a loss-of-function mutant of a closely related family member, AGL18, show decreased ability to produce somatic embryos. If constitutive expression of orthologs of AGL15 is able to enhance somatic embryo development in other species, thereby facilitating recovery of transgenic pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
138
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 146 publications
(144 citation statements)
references
References 44 publications
5
138
0
1
Order By: Relevance
“…Other genes have been identified that, when ectopically expressed, are able to promote somatic embryogenesis, including WUSCHEL (Gallois et al, 2004), BABY BOOM (Boutilier et al, 2002), SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KI-NASE1 (Hecht et al, 2001), LEAFY COTYLEDON 1-LIKE (Kwong et al, 2003) PGA37/MYB118 and MYB115 (Wang et al, 2009), and AGAMOUS-LIKE15 (AGL15; Harding et al, 2003;Thakare et al, 2008). Loss-of-function mutants in most of these genes do not have defects during zygotic embryo development, perhaps indicating the presence of redundant factors, as is common with ;90% of gene functions protected by redundancy (Pickett and Meeks-Wagner, 1995;Meinke et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other genes have been identified that, when ectopically expressed, are able to promote somatic embryogenesis, including WUSCHEL (Gallois et al, 2004), BABY BOOM (Boutilier et al, 2002), SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KI-NASE1 (Hecht et al, 2001), LEAFY COTYLEDON 1-LIKE (Kwong et al, 2003) PGA37/MYB118 and MYB115 (Wang et al, 2009), and AGAMOUS-LIKE15 (AGL15; Harding et al, 2003;Thakare et al, 2008). Loss-of-function mutants in most of these genes do not have defects during zygotic embryo development, perhaps indicating the presence of redundant factors, as is common with ;90% of gene functions protected by redundancy (Pickett and Meeks-Wagner, 1995;Meinke et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Ectopic expression of AGL15 promotes development of somatic embryos from zygotic embryo explants and then maintains development in this mode for extended periods (over 12 years to date; Harding et al, 2003). A 35S pro :AGL15 transgene also promotes somatic embryo development from the shoot apical region of seedlings that had completed germination in liquid media containing 2,4-D (Harding et al, 2003;Thakare et al, 2008). Furthermore, a putative ortholog of AGL15 from soybean (Glycine max) enhanced somatic embryo development in this species (Thakare et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ectopic expression of BBM results in the formation of somatic embryos and cotyledon-like structures on seedlings [15]. Moreover, overexpression of the Arabidopsis AGAMOUS-Like 15 (AGL15) gene and its homologous gene in soybean, which encode MADS domaincontaining proteins, enhances the formation of secondary embryos and somatic embryos [16,17]. The promotion of somatic embryo formation by AGL15 is attributed, at least in part, to a reduced GA level [18].…”
Section: Introductionmentioning
confidence: 99%
“…Other genes encoding transcription factors also promote embryo development when ectopically expressed, including BABY BOOM (BBM; Boutilier et al, 2002), WUSCHEL (Zuo et al, 2002;Gallois et al, 2004), LEAFY COTYLEDON1-LIKE (L1L; Kwong et al, 2003), PLANT GROWTH ACTIVATOR37/MYB118 and MYB115 , and AGAMOUS-LIKE15 (AGL15; Harding et al, 2003;Thakare et al, 2008). SOMATIC EMBRYO-GENESIS RECEPTOR-LIKE KINASE1 (Hecht et al, 2001) encodes a Leu-rich repeat receptor-like kinase, but it too promotes somatic embryo formation in some systems when expressed via the 35S promoter.…”
mentioning
confidence: 99%